Vehicle Accident Detection System using Accelerometer - Azlan, Hanif Hakimi; Salimin, Suriana (Evolution in Electrical and Electronic Engineering, 2023)
Generally, road lane design and heavy traffic control accidents still happen significantly despite the presence of so much contemporary equipment in vehicle design. Because no medical facility was accessible at the appropriate time and location in the majority of accidents, people died. Thus, this paper intends to lower this risk factor using an automatic accident detection system. Using a microcontroller technology like the ESP32 NodeMCU, any accident can be detected automatically. A vehicle’s tilt or vibration during an accident is detected using the MPU6050 detector that is connected to the MPU 6050. The Global Positioning System (GPS) module tracks the accident’s location and the GSM module sends an SMS/message to a predetermined number. By utilising GPS and sensors, this automatic tracking system can help track and locate the precise location of any vehicle that has been in an accident. This project’s outputs include a piezo buzzer, LCD, and LED (green and red). Except for the LED (green), all results are used to alert the surrounding area when a traffic accident occurs. The 6V PV solar panel used in this project absorbs solar energy, converts it to electricity, and charges the Li-on 18650 3.7V battery with a capacity of 2000 mAh and increases the voltage to 5V as an output, which will be used as a power supply for the ESP32 in this project. Furthermore, the current findings show that the system is able to identify accidents and send SMS/messages and the location to a predetermined number by putting all the systems in the junction box.